Chemokines: more than just road signs. - Bachmann, M; Kopf, M; Marsland, B (2006)
Chemokines have long been known to orchestrate dendritic-cell migration in the body. However, recent evidence has shown that chemokines not only direct the trafficking of dendritic cells but also can regulate their maturation status. Here, we propose that this dual function of chemokines ensures that T cells and dendritic cells meet in T-cell regions of lymphoid organs and that antigen is presented in an immunologically optimal context for T-cell priming.